A comparative study of the successful management of religious diversity: Melbourne and Hong Kong - Bouma, Gary D.; Singleton, Andrew (2004)
The study of the management of religious diversity has largely proceeded non-comparatively at national and organizational levels. As a result it is not yet possible to declare what promotes and what hinders the emergence of harmonious inter-religious relations in religiously diverse societies. This article compares the management of religious diversity at an urban level through a comparison of Melbourne, Australia and Hong Kong. The article first describes the demographic history of these two cities and then explores their social institutions of religion and organizations promoting inter-religious harmony in order to find explanations for the postwar emergence of societies characterized by both religious diversity and inter-religious harmony. Finally, it reflects on the policy implications of these findings. - Reproduced.
Keywords: Religious institutions